A práxis Educativa no Contexto de Grupos de Discipulado na Igreja Comunidade da Graça - Souza, Marcelo José de (2008)
This text is a theoretical research that seeks to present the implications of educational practices in the context of discipleship groups of Comunidade da Graça . The objective of this study is to analyze and identify discipleship s educational function within the context of the local church. The approach is according the theological and ecclesiastical conceptualizations of the works of Dietrich Bonhoeffer and Karl Barth. The educational focus is based on the work of Thomas Groome. This way, a theological and also an educational perspective are established in face of the object of study. It is our objective to inform about the dialog between discipleship theory and the actual practice in the local church. We present the theories for the theological conceptualization of discipleship as well as a theory for its contextualization in the field of Christian Education, seeking to identify similarities and differences between the practice in these and the practice at the headquarters of Igreja Comunidade da Graça in São Paulo. We use comparative methodology, seeking to develop a dialog between theory and practice, with the objective of raising questions regarding that practice. In summary, we verified that the practice of the discipleship groups of Comunidade da Graça present limitations as well as contributions towards Christian Education practice.(AU)